Syringomyelia in preterm children with posthemorrhagic occlusive hydrocephalus - Weinzierl, Martin; Honnef, Dagmar; Assmann, Birgit (Child's nervous system, 2012)
Objective and importanceWhereas posthemorrhagic hydrocephalus is well known after preterm birth, its association with syringomyelia has been reported only once. Here, we describe two additional patients showing this rare constellation.Clinical presentationThe children had been born after 27 and 28 completed weeks of gestation, respectively. Both had developed neonatal cerebral hemorrhages. At the age of 4 years, patient 1 presented with progressive ataxia leading to the diagnosis of internal hydrocephalus and extensive syringomyelia. In patient 2, progressive ventriculomegaly and syringomyelia were diagnosed at the age of 4 weeks.InterventionIn both children, ventriculoperitoneal shunting resulted in clinical improvement, decrease of the ventricular size, and regression of the syringomyelia. After surgery, patient 1 developed a subdural hematoma and patient 2 parenchymatous cerebral hemorrhages.ConclusionThe combination of syringomyelia and posthemorrhagic hydrocephalus may be more frequent than commonly assumed. Therefore, neurological deterioration may mandate spinal MRI in addition to cerebral MRI. Syringomyelia seems to result from impaired ventricular cerebrospinal fluid drainage as it regresses after ventriculoperitoneal shunting. Bleeding may complicate the postsurgical relaxation of distended brain parenchyma.
Gesehen am 07.05.2019